Comparison of copper IUDs and hormonal IUDs in prevalence of Candida species in cervicovaginal smears - Wei, Tao; Wang, Hua; Wen, Boyang (Cellular and Molecular Biology, 2022)
Candidal vulvovaginitis is one of the most common genital infections that different types of diagnosis are essential for a proper treatment plan. IUD is one of the most influential and long-lasting methods of contraception that can be associated with vaginal candidiasis. This study was performed to investigate the prevalence of Candida species before and three months after IUD placement in patients referred to health centers. Also, a comparison of copper IUDs and hormonal IUDs was evaluated to consider the prevalence of Candida species in cervicovaginal smears. In this regard, cervicovaginal swabs were prepared from 160 women applying for IUDs who did not show signs of vaginal infection during the vaginal examination. These people were divided into two groups of 80 cases. The first group received copper IUDs (NT Cu380, Mona Lisa®, Canada), and the second group received hormonal IUDs (Mirena, USA). They had not used antibiotics or antifungal drugs at least two weeks before and three months after IUD placement. The provided Samples were cultured in a Saburo dextrose agar medium. The milky yeast colony was transferred to chromium agar culture medium, and fungal species were differentiated by dyeing. P <0.05 was considered significant. Three months after IUD insertion, 29.57% of people who received a copper IUD were diagnosed with candidiasis. Also, different species of Candida were observed in 22.95% of people who received hormonal IUD. Because Candida albicans is found in the vaginal microflora of 30 to 80% of asymptomatic women, the decision to treat asymptomatic cases requires further study and testing. The use of Candida chromium agar differential culture medium is easy, reproducible, and cost-effective; however, in cases such as recurrent or complicated vulvovaginal candidiasis where the accurate diagnosis is essential for successful treatment, the use of sensitive and precise molecular methods such as PCR is recommended. Finally, studies with wider dimensions and longer follow-up periods are suggested to confirm and complete the present study.